Proteç\~ao social dos trabalhadores de plataformas digitais: Experiência internacional - América Latina e Europa - Leonardo Alves Rangel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The global economy is undergoing profound transformations, commonly referred to in the literature as the Fourth Industrial Revolution. Among the ramifications of these shifts, a notable aspect is the impact on labor relations. Specifically, there is a notable uptick in the number of individuals engaging in various tasks through digital platforms. These roles typically lack social protection and, despite their potential for rapid income generation, often entail considerable income volatility. The challenge that arises is how to protect this growing number of platform workers. This study presents the experience of a group of countries in Latin America and Europe, as well as the proposal under discussion within the European Union regarding the regulation of digital platform workers. Diverse approaches adopted by nations to address this issue are outlined. While recognizing the imperative of extending social protection to these workers, there is also a recognition of the necessity to ensure the long-term sustainability of social protection systems.
Keywords: H55; J83; 330; digital platforms; social protection